Optimalisasi Desain Instruksional untuk Meningkatkan Efektivitas Pembelajaran Bahasa Indonesia di Sekolah Dasar: Optimization of instructional design to enhance the effectiveness of Indonesian language learning in elementary schools - Solihudin, Muhamad; Chamalah, Evi (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
This study aims to analyze and develop effective instructional designs for teaching Indonesian language in elementary schools. The main problems identified include low student motivation, difficulties in reading comprehension, limited learning media, and minimal student engagement during the learning process. This study uses a qualitative method with a descriptive-analytical approach through observation, teacher interviews, and literature study. The results show that the application of instructional design based on a constructivist approach, the use of visual and digital media, and the application of active learning strategies can improve students' conceptual understanding, reading interest, and literacy skills. In addition, student engagement in learning increased significantly when teachers acted as facilitators and mentors. This study recommends the development of adaptive, contextual, and student-centered instructional designs to create a more interactive, meaningful, and relevant Indonesian language learning process that meets the developmental needs of elementary school students.